Topik yang saya akan bahas kali ini adalah tentang pelayanan BPJS Kesehatan melalui aplikasi Mobile JKN, khususnya dalam pemberian informasi dan pelayanan. Mobile JKN merupakan suatu inovasi terbaru pelayanan jaminan Kesehatan nasional yang berbasis elekt - Gilbert Parera; Muhammad Darwis (bit-Tech, 2023)
Mobile JKN is a new Government application to register and manage the health protection membership. The problem that often occurs is that many participants do not really understand the application and their use. Therefore, JKN mobile application needs to be adjusted and developed so that the usefulness and benefits can be felt by the participants and the wider community. The method used is the System Usability Scale (SUS), a questionnaire that can be used to measure the usability of a computer system according to the user's subjective point of view. In performing SUS calculations using 5-point Likert scale. The first SUS score was obtained from testing the JKN Mobile Application by distributing SUS questionnaires to 23 respondents.  The second test was carried out by involving 3 professionals and experts in the science of design and IT. The treatment of the SUS questionnaire in the second test was by adding points of recommendation for improvement to the Mobile JKN application in accordance with the first results in each statement of the second test questionnaire. And the results of the SUS score in this second test experienced a significant increase from 59 to 81, this shows that the recommendations for improvements to the Mobile JKN application need to be improved or need to be developed a lot. The Mobile JKN application needs to be developed a lot in terms of updating and providing information about this application because there are still many and do not understand about the Mobile JKN application.